Delta extraction in a limited collaborative environment. (2015) - Lu, Zheng; Liu, Haijun; Yan, Jun
This work considers extracting delta in a distributed environment where the collaboration from highly autonomous operational database management systems is limited to granting read only access on a set of selected relational tables. In addition, due to possibly large volumes of remote source data involved, and consequently enormous overhead associated with data transfer, efficiency issues must been taken into consideration. This research is based on the observation that usually, there is a large amount of static data in relational tables. It is proposed to use some statistical techniques in data warehouse system to help us understand the essential characteristics of remote data. Based on the characteristics of remote data, some optimisation techniques are presented.